Analysis of Selected Elements of Knowledge Management Systems in the Context of the Basics of Their Functioning - Rafal PRUSAK; Edyta KARDAS (Communications of International Proceedings, 2021)
The ability to learn and develop as well as to convey knowledge are considered to be fundamental issues from the point of view of growth and survival of an organization and building a competitive advantage. Knowledge is the basis for understanding the processes taking place in the environment, relations between individual market entities and the effects of individual resource allocation models. In accordance with the opinion that is expressed more and more frequently by specialists, knowledge – on a micro scale – is presently becoming a priority production factor and – on a macro scale – a determinant of technical progress. In this paper, the attempt of identification and evaluation of selected elements of knowledge management was made. It presents the results of research in the area of general assumptions of the knowledge management system. A general analysis of the obtained results was performed, also the research results in the context of the size of enterprises and the type of their activities were presented. The study was made in the group of 105 enterprises located in the southern part of Poland.
Keywords: Knowledge Management; Efficiency of Enterprise.